A multi-surface model for ferroelectric ceramics - application to cyclic electric loading with changing maximum amplitude. Issue 13 (2nd May 2016) - Maniprakash, S.; Arockiarajan, A.; Menzel, A.
Abstract : Depending on the maximum amplitude of externally applied cyclic electric fields, ferroelectric ceramics show minor or major hysteresis. The materials also show asymmetric butterfly hysteresis in a prepoled material. Aiming at capturing these behaviour in a phenomenological constitutive model, a multi-surface modelling approach for ferroelectrics is introduced. In this paper, with the note on the motivation for a multi-surface model related to the results of new experimental investigations and also to experimental data reported in the literature, the constitutive relation for a rate dependent multi-surface ferroelectric model is developed. Following this, a brief graphical illustration shows how this model captures the objective phenomena. Consequently, the numerical implementation of the model to capture experimental results is demonstrated. Finally, the performance of this model to represent behaviour of decaying polarisation offset of electrically fatigued specimen is shown.